Pengaruh Pemberian Labu Siam Dan Mentimum Terhadap Penurunan Tekanan Darah Pada Penderita Hipertensi Di Wilayah Puskesmas Cimanggu Kabupaten Pandeglang Banten: The Effect of Giving Siamese Pumpkin and Cucumber on Lowering Blood Pressure in Hypertension Patients in Cimanggu Health Center, Pandeglang Regency in Banten - Puji Lestari, Sri Pertiwi; Saputri, Milla Evelianti (Dohara POAJ, 2023)
Introduction: Hypertension continues to increase every year, Pandglang Regency is the district with the highest presentation of hypertension with a total of 622,060 cases. The incidence of hypertension at the Cimanggu Health Center has increased every year. One way of a good diet is to reduce salt intake and increase potassium intake. Giving chayote juice and cucumber juice has high potassium which can lower blood pressure. Methods: Quasi-experimental design with pretest-posttest design with control group design. There were 56 samples in this study with 28 respondents in each group using the purposive sampling technique. Data analysis used paired sample t-test and Independent T-Test which were previously tested for normality and homogeneity. Results: The difference in the average value of blood pressure given by chayote was at systole 26,43 mmHg and 27,79 mmHg at giving chayote is more effective in reducing blood pressure in hypertensive patients than cucumber with a posttest systolic p-value of 0,007 and 0,000 diastolic. Discussion: Giving chayote is more effective in reducing blood pressure in hypertensive patients than cucumber. It is expected that people with hypertension besides using medicines from doctors can also use chayote juice or cucumber juice.